PERTUMBUHAN DAN HASIL DUA KULTIVAR PADI DAN BERBAGAI JARAK TANAM PADA SISTEM PENGAIRAN GENANGAN DALAM PARIT - Syamsuddin Syamsuddin; Didik Indradewa; Bambang Hendro Sunarminto; Prapto Yudono (Agroland: Jurnal Ilmu-ilmu Pertanian, 2011)
The experiment was conducted on the Technical Irrigated Rice Field in D.I. Yogyakarta with soil type is Regosol. The study took place in July to December 2010. The research aim was to obtain agronomic characters and optimal planting distance that could increase the productivity of land with furrow irrigation system (FIS). The research used a factorial design (2 x 4+2) with 3 replications. Factor 1 was cultivars (K): K1 (Cimelati) and K2 (Sarinah). Factor 2 was planting distances (J): J1 (20 x 20 cm), J2(20 x 15 : 40 cm; legowo 2:1), J3(20 x 12,5 : 40 cm; legowo 2:1), and J4(20 x 12,5 : 45 cm; legowo 2:1). Controls were Cimelati and Sarinah cultivars grown in wetland rice field. The experimental results showed that the ability of plants to form seedlings in FIS was better than in the rice fields. The ability of plants to form seedlings in FIS at different planting distances was similar. Net assimilation rate (NAR) and relative growth rate (RGR) in the wetland system was better than FIS, but the leaf area index (LAI) and crop growth rate (CGR) was better in FIS. The NAR, RGR, and CGR in both systems were similar. Larger panicle and grain panicle number, 1000 grain weight and percentage of filled grain rice were found in FIS than in the rice field. The growth of rice in FIS was not affected by differences in both cultivars and planting distance. Dry harvested grain weight in FIS was lower than in the rice field. Dry harvested grain weight of Cimelati cultivar (8.04 t/ha) in FIS with planting distance of 20 x 12,5 : 40 cm (legowo 2:1) was comparable with that in the rice field (8.05 t/ha).